ANALISIS DAMPAK PENERAPAN PSAK 72 TERHADAP KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI DI MASA PANDEMI COVID-19 - Duwi Rahayu (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This study aims to determine how the impact of the application of PSAK 72 on the financial performance of telecommunications companies during the Covid-19 pandemic. This research was conducted in the telecommunications sector, which was affected by the issuance of PSAK 72. This research uses descriptive quantitative analysis techniques. The sampling technique uses non-probability purposive sampling technique, namely telecommunication companies listed on the Indonesia Stock Exchange that meet the predetermined criteria. The following three telecommunication companies which become the research sample, namely PT. Telekomunikasi Indonesia Tbk, PT. INDOSAT Tbk AND PT. XL AXIATA Tbk. The results of this study indicate that the application of PSAK 72 resulted in the financial performance of the three companies not being a little better when compared to the previous standard. The difference in the revenue recognition provisions based on PSAK 72 and the previous standard caused a slight change in the value of revenue from contracts with customers in the third quarter of 2020, so that the revenue value was smaller when compared to using the previous standard. On the other hand, based on the assessment of the three companies, the Covid-19 pandemic has not had a significant adverse impact on the business continuity of PT Telkomsel Indonesia Tbk, PT. INDOSAT Tbk and PT. XL AXIATA Tbk.